Videogames and open feedback systems to enhance probabilistic reasoning and engagement - Andres Felipe Velasco Hernández; David Sebastián Baldeón Padilla; Andrés Adolfo Navarro Newball (Serious Games Society, 2024)
This study analyzed the relationship between probabilistic reasoning, feedback type, and engagement across four sessions of an DGBL educational practice with a feedback system. Results show that engagement and probabilistic reasoning varied longitudinally during the intervention. In addition, the teacher's feedback was found to be of an open-ended type. Significant correlations were established between probabilistic reasoning and feedback, as well as between engagement and probabilistic reasoning in one of the sessions. Implications for teaching and designing DGBL sequences are presented.